RELIEF CANDI SEBAGAI MEDIA EFEKTIF UNTUK MENYAMPAIKAN INFORMASI MORAL-DIDAKTIF PADA MASA JAWA KUNA - Lelono, Hari (Berkala Arkeologi, 2016)
The establishment of temple as sacred buildings of Shivaism/Buddhism in Ancient Javanese Period aimed to worship gods. Temples are, decorated by reliefs contain moraleducationalÂ message to support their aim. Stories or non stories depicted on the relief functioned as information/publication medium for adult as well as children. This article examines why relief was used in Hinduism-Buddhism Period to deliver moral-educational message to them. Methods used is observation on the relief stories carved on temples in Central and East Jav, analysis, and interpretation based on literature study.